The study of metaphor application in Vassafâs History - Ali reza mahmoodi (Literary Arts, 2015)
Abstract Tajziyat ol-Amsar and Tazjiyat ol-Asar which is called Â Vassafâs History Â had been written by Adib Shahab od-Din Fazl ol-Lah Shirazi (born in 663 H.) who was titled âVassaf al-Hazraâ and is known as âVssafâ. The subject of this book is related to the history of âIlkhanianâ, the kings in Iran from 656 to 72 H., the author considers it as a complement for Jahangosha Jovainiâs Histiory. Vassafâs History is a notable historical-artistic (technical) literary work. Euphuism prose or artistic prose is an ornated prose which is a genethliacum according to the different figures of speech, spiritual ornament and speech amplification by various descriptions, illustration, poetry, Persian and Arabic evidences and the usage of different science expressions inter-textually. The artistic prose has a close relationship with poeticalness. Some literary researches equal it to poetry based on emotional and poetical aspects of artistic prose. Â Â  Vassaf al-Hazra tried to compose Vassafâs History in order to develop a historical book into a famous and valuable literary-historical text through a poetical language. He has tried to create an ornament, beautiful, poetical and historical- precise text by using figures of speech and literary devices. Â Â  The goal of this paper is to show the literary beauties of this book. The author tried to show the usage of various metaphors and ambiguity through descriptive and analytic method and conventional eloquence. The result of this research shows the specific attention of Vassaf to the use of poetic image. This application includes extended metaphor, metaphoric prediction and explicit metaphor. The application of metaphor in addition to poetic images create an individual style, this style is not very obvious in other historical-artistic texts because of the position of poetic images, with figurative and unfamiliar words and a lot of evidences. The existence of precise specially in explicit metaphor and metaphoric prediction in Vassafâs History that is in relationship to emotive language, are the effective factors in Vassafâs History in comparison to other historical- artistic texts.